Mentoring Student Learning Activities to Increase Student Achievement Motivation at the Sentul Guidance Studio, Kuala Lumpur, Malaysia - Rachmad Chartady; Ananda Putri Sephiani; Siti Dena Zahara; Vandi Verdiansyah; Anggraini Diah Hardaya Putri; Shohehuddin Shohehuddin (International Journal of Community Engagement and Development, 2023)
Education is one thing that is very beneficial for every human being. This education can make people become quality individuals who can increase their honor and dignity. Sentul Tutoring Studio is one of several learning studios established in Peninsular Malaysia to provide education to children living around the Sentul area, Kuala Lumpur. Students at Sentul Guidance Studio are undocumented/non-documented children of Indonesian migrant workers. This service aims to provide achievement motivation among the students of Sanggar Guidance Sentul Malaysia. The method used is a participatory method, where this method is carried out in the process of problem solving or decision making which actively involves all parties involved in the process. This service activity involved 35 students from the Sentul Malaysia Guidance Studio. The conclusion of this service is that students can develop achievement motivation and self-confidence in what they want, where in this service the focus is on the ideals that students have.